(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Financial planning is industries that emerge from the desire of households to receive financial advice from a single source. According to the Financial Planning Association, a main industry organization representing financial planners, financial planning is a process that involves taking stock of all existing resources of individuals, developing a plan to utilize them, and systematically implementing the plan in order to achieve short- and long-term goals of individuals.